In-situ Interfacial Passivation for Stable Perovskite Solar Cells - Duan, Longfan; Li, Liang; Zhao, Yizhou; Cao, Guangyue; Niu, Xiuxiu; Zhou, Huanping; Bai, Yang; Chen, Qi (Frontiers in Materials, 2019)
Unreacted lead iodide is commonly believed playing an important role in the performance of perovskite solar cells. However, the excess lead iodide acts like a double-edged blade, which hampers the long-term stability of devices. Here, we used the ethanedithiol (EDT) as the solvent to process Spiro-OMeTAD (Spiro) layer. Due to the strong coordination between EDT and Pb (II), the unreacted PbI2 at the perovskite films surface was effectively passivated, which suppressed the degradation of the perovskite layer without sacrificing the efficiency. Moreover, the hydrophobic EDT also enhanced the moisture stability of devices, thus prolonged the device lifetime. With EDT-Spiro layer, a stabilized power conversion efficiencies from 17.11% up to 19.23% was achieved in the corresponding device. More importantly, a significant enhancement of the long-term stability of perovskite solar cells was observed under the N2 atmosphere without sealing for 30 days.